Hereditary renal tubular disorders: Single Iraqi center experience of 80 pediatric cases - Ahmed Azat, Nariman F. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Hereditary renal tubular disorders (HRTDs) encompass various clinical syndromes and most of them have profound effects on child’s growth and development,. Patients and methods: We reviewed the medical records of eighty children (48 males and 32 females) seen over an eight years period from (sep.2004-may2012) at children welfare teaching hospital.Objectives: was to review our experience at children welfare teaching hospital in Baghdad with the various types of HRTDs and delineate the spectrum of clinical expression and outcome. Results: The distribution of patients according to HRTD was as follows: (56.25%) proximal RTA (pRTA), (30 %) distal renal tubular acidosis (dRTA), (2.5%) type IV RTA, (10%) Bartter’s syndrome and (1.25%) Gitelman syndrome. Age at diagnosis ranged between 1 month and 16 years. Overall, consanguinity rate was as high as 85%. Rate of affected siblings was 58.75%. Failure to thrive was common symptoms in all our patients’ with HRTDs. Renal failure was found in (24.4%) of patients with pRTA and 25% of patients with dRTA. Hearing loss was present only in patients with dRTA (20.8%). Convulsions were noted in (37.7 %) of patients with pRTA, (16.6 %) patients with dRTA and the patient with Gitelman syndrome. Nephrocalcinosis were more common in dRTA patients (79.16%). Conclusions: The high rate of consanguineous mating is likely to produce many heritable disorders including HRTDs by increasing the knowledge on demographic, clinical, and laboratory features of this rare disease group may serve to increase our current knowledge on this disease group making early diagnosis and life-saving treatment possible.